Skid Resistance Analysis Due to Rubber Deposits on the Runway of Sultan Babullah Ternate Airport - Hi Umar, Sudirman; Shandy, Sary (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
Rubber deposit is the thickening of the rubber layer on the runway surface as a result of the friction of the rubber of the aircraft wheels during take-off and landing, resulting in the risk of the danger of aircraft slipping if the aircraft takes off and lands on the runway surface. Rubber deposit cleaning is carried out depending on the high frequency of aircraft movements on the runway per day. The research stage begins with observation and collection of data on the measurement of runway conditions, especially in the aircraft touch down area, carrying out observations on the process of cleaning rubber deposits in the aircraft touch down area, collecting the results of measuring the roughness test value before and after cleaning, analyzing the roughness value of the runway before and after cleaning. The results of the study found that the number of flight traffic at Babullah Airport per week is 155 flights or as many as 620 flights within one month, and the average number of aircraft landings at Babullah Airport is 313 times, so if you refer to KP 94 of 2015 concerning the rubber removal cleaning schedule on the runway of Babullah Airport with a routine cleaning schedule of 1 time in 1 year. Then there is a difference in the value of skid resistance at Sultan Babullah Airport with varying values, at the test point center line 31 – 14 has a value of before cleaning of 0.48 then after cleaning the value of the cleanliness becomes 0.70 as well as the test point at 6 meters left 14 – 32 has a roughness value of 0.59 before cleaning and 0.82 after cleaning/removal, The average value of runway roughness before cleaning was 0.53 and the average value of roughness after cleaning.